Assessing customer passion, commitment, and word-of-mouth intentions in digital assistant usage: The moderating role of technology anxiety - Daniel K. Maduku (17337748) (2023)
Consumers develop a passion for the use of innovations, which is a critical determinant of their success. Research has largely examined drivers of initial acceptance of digital assistants (DAs) and has yet to fully understand the factors driving or deterring consumers’ passion towards DAs and the behavioural outcomes. Drawing on the stimulus-organism-response framework, this study examines a unique set of factors (usefulness, ease of use, privacy concern, and localisation) that act as stimuli to drive an organismic state of passion for DAs, and how this produces behavioural responses of word-of-mouth (WOM) intention and commitment to DA use. The study also examines how technology anxiety moderates passion’s impact on WOM intentions and commitment. The findings show that usefulness, ease of use, privacy concern, and localisation are significant explanatory variables of consumers’ passion towards DAs. Furthermore, passion towards DAs results in WOM intentions and commitment to its use. The findings further show that passion’s effect on DAs in explaining WOM intentions and commitment is weakened by technology anxiety. Lastly, passion is the mediating mechanism through which usefulness, ease of use, privacy concern, and localisation impact WOM intentions and commitment. The implications of these findings for theory and practice are highlighted. Other Information Published in: Journal of Retailing and Consumer Services License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jretconser.2022.103208